Javanese Speech Levels and Language Politeness Among First-Grade Elementary Students: A Sociolinguistic Study - Dwi Wulandari; Samia Al-Shidi; Torebaeva Firuza (Journal of Language, Literature, and Educational Research, 2026)
Purpose of the study: This study aims to describe the use of Javanese speech levels by first-grade students at Public Elementary School 2 Trnten, Candimulyo, Magelang, including the types of speech levels used, the factors influencing their use, and the communicative functions reflected in daily school interactions. Methodology: This study employed a descriptive qualitative method. The subjects were 16 first-grade students of Public Elementary School 2 Trenten, Candimulyo, Magelang. Data were collected through observation, interviews, field notes, recording using a recorder, and note-taking techniques. Data analysis used descriptive analysis with semantic validity and intra-rater reliability. Main Findings: The findings showed four types of Javanese speech levels used by students: ngoko lugu, ngoko alus, krama lugu, and krama alus. The use of speech levels was influenced by interpersonal formality, place and situation, communicative purpose, and social norms. Their functions reflected intimacy in ngoko and respect in krama interactions. Novelty/Originality of this study: This study specifically examines Javanese speech level usage among first-grade elementary students in natural school interactions, highlighting early language politeness development. It contributes to sociolinguistic studies by showing how children apply unggah-ungguh basa Jawa in real educational contexts and social communication practices